A Qualitative Approach to a Better Understanding of the Problems Underlying Drug Shortages, as Viewed from Belgian, French and the European Union’s Perspectives - Bogaert, Petronille; Bochenek, Tomasz; Prokop, Anna; Pilc, Andrzej (PLOS ONE, 2015)
The problem of drug shortages has been reported worldwide, gaining prominence in multiple domains and several countries in recent years. The aim of the study was to analyze, characterise and assess this problem in Belgium and France, while also adopting a wider perspective from the European Union. A qualitative methodological approach was employed, including semi-structured interviews with the representatives of respective national health authorities, pharmaceutical companies and wholesalers, as well as hospital and community pharmacists. The research was conducted in early 2014. Four themes, which were identified through the interviews, were addressed in the paper, i.e. a) defining drug shortages, b) their dynamics and perception, c) their determinants, d) the role of the European and national institutions in coping with the problem. Three groups of determinants of drug shortages were identified throughout this study: manufacturing problems, distribution and supply problems, and problems related to economic aspects. Currently, the Member States of the European Union are striving to resolve the problem very much on their own, although a far more focused and dedicated collaboration may well prove instrumental in coping with drug shortages throughout Europe more effectively. To the best of the authors’ knowledge, this is the first qualitative study to investigate the characteristics, key determinants, and the problem drivers of drug shortages, focusing on this particular group of countries, while also adopting the European Union’s perspective.